City of bones - Clare, Cassandra (Clare, Cassandra. Mortal instruments, 2007)
Suddenly able to see demons and the Shadowhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizarre world when her mother disappears and Clary herself is almost killed by a monster.